Sea urchins (Tripneustes gratilla) as dispersal agents of the coral Montipora digitata in Bolinao, Pangasinan - Merciales, Rey Vincent C.; Parangat, John Kelly R.; Villariza, David Gwynfor G.
Sessile marine organisms, particularly those that do not rely on planktonic propagules for propagation, depend on abiotic and biotic agents of dispersal. Montipora digitata, a branching coral known to propagate by fragmentation, occurs in isolated yet extensive patches in sandy, shallow reef areas in Bolinao, Pangasinan. The area is also the habitat of various echinoderms, the most prominent of which is the sea urchin, Tripneustes gratilla, which is known to pick up fragments of rock and algae to hide itself. This study explores the potential role of the collector urchin, T. gratilla, in the observed encroachment of M. digitata. Different tests were conducted including the test for preference of sea urchins on live or dead coral fragments, distance travelled by the urchin with these fragments, survivorship of coral fragments as well as clonal dispersion of fragments as determined from histocompatibility tests. Results suggest that although the T. gratilla have a preference for dead coral fragments (61%), it was still able to pick up live fragments 39% of the time. Deviations from this preference might have been accounted for by differences in the composition of the live and dead fragments and on the interaction between the sea urchin's tube feet and the fragment it adheres to. The distance travelled by the T. gratilla while carrying the M. digitata fragments showed no significant difference between the fragment's different sizes. On the other hand, the distance travelled for the fragment is positively correlated to the time elapsed. Results from the survivability test showed that after two months of observation, surviving M. digitata grew larger in size and become more pigmented. This was also observed in the histocompatibility test wherein fragments did not fuse but continue to grow -- Author's abstract.